Effects of NSAIDs and environmental oxygen pressure on bone regeneration - Victor Chumpitaz-Cerrate; Lesly Chávez-Rimache; César Franco-Quino; Elías Aguirre-Siancas; Victoria Caldas-Cueva; Eliberto Ruíz-Ramírez (Universidad de Concepción., 2019)
Objective: To evaluate the effects of administering diclofenac and ketoprofen, as well as the effects of environmental oxygen pressure variation on mandibular bone regeneration. Methods: Thirty-six guinea pigs were distributed into two equal groups. Mandibular bone defects were performed on both groups. Group A was monitored under oxygen pressure at altitude (3320msl, 107mm Hg). Group B was monitored at sea level oxygen pressure (150msl, 157mm Hg). Each group was subdivided into 3 equal groups (A1, A2, A3 and B1, B2, B3). Subgroups A1 and B1 were given diclofenac; subgroups A2 and B2 ketoprofen; subgroups A3 and B3 NaCl. Bone regeneration was evaluated histologically on days 15 and 30. Results: After 15 days in the group controlled at sea level, the level of osteoblasts presented by the control subgroup was significantly higher (28.00±2.65) compared to the diclofenac subgroup (16.00±6.25) and to the ketoprofen subgroup (18.00±4.36); (p=0.041). After 15 days in the group controlled at altitude, the level of osteoblasts was significantly higher in the control subgroup (38.00±5.29) compared to the diclofenac subgroup (21.67±6.35) and to the ketoprofen subgroup (19.33±2.52); p=0.007. After 30 days in the group at sea level there was no difference found in the cell counting; p>0.05. After 30 days in the group controlled at altitude, the level of osteoblast was significantly higher in the control subgroup (58.00±4.58) compared to the diclofenac subgroup (34.33±4.73) and the ketoprofen subgroup (34.00±11.14); (p=0.003). Conclusion: The administration of diclofenac and ketoprofen produced lower mandibular bone regeneration, the effect being significantly more negative at sea level.